Challenges of Teaching Presence and SDL Scaffolding: A Systematic Literature Review on Dominant Pedagogical Barriers in Blended Learning Implementation in Higher Education - Rina, Nova; Satria, Willy (Universitas Islam Negeri Palopo, 2025)
This Systematic Literature Review (SLR) provides an in-depth analysis of pedagogical barriers in Blended Learning (BL) within higher education, specifically focusing on challenges related to Teaching Presence (TP) and the scaffolding of Self-Directed Learning (SDL). While previous reviews have largely focused on infrastructural constraints, there is a scarcity of synthesis regarding design-centric pedagogical barriers. A rigorous PRISMA-compliant SLR protocol was applied to 20 empirically-driven studies published between 2021–2023 across diverse disciplinary contexts. Data were extracted based on predefined criteria and analyzed using qualitative thematic synthesis. Pedagogical barriers were frequently reported (identified in 90% of studies). Key challenges clustered around: (1) Deficient TP in Course Design (failure to cohesively integrate online and face-to-face activities) and (2) Inadequate SDL Scaffolding (failure to provide explicit guidance for student self-monitoring). This synthesis posits that technical constraints are often secondary consequences of foundational pedagogical design flaws. The findings establish that a primary bottleneck in contemporary BL implementation is pedagogical, offering a foundation for institutions to prioritize faculty development in instructional design.